Institutional Structure and Environmental Pollution: An Application within the Framework of the Environmental Kuznets Curve Hypothesis - Hayaloglu, Pınar; Recepoglu, Murşit; Cakir, Mehmet Ali (International Journal of Energy Economics and Policy, 2025)
The EKC hypothesis explains the relationship between economic growth and environmental degradation. However, criticisms of its fundamental assumptions suggest that this relationship should be examined more comprehensively. While the EKC hypothesis addresses the link between income levels and environmental quality, it may overlook the impact of institutional structures and policy factors. In this context, recent studies increasingly highlight the role of institutional structures in environmental degradation. Accordingly, this study aims to provide a comprehensive analysis of environmental sustainability by approaching the EKC hypothesis from the perspective of institutional quality. To determine the effects of institutional quality on environmental degradation, the study employs the Driscoll-Kraay estimation method. The analysis is conducted on a sample of SADC countries for the period 1990-2021. The findings indicate that institutional quality has a statistically significant and positive effect on environmental degradation; however, beyond a certain threshold, this effect reverses. Additionally, the impact of economic growth on environmental degradation is examined within the EKC framework, revealing that while per capita income initially increases environmental degradation, exceeding a certain income level leads to improvements in environmental quality. The findings confirm the validity of the EKC hypothesis in SADC countries and suggest that strong institutional structures can play a supportive role in promoting environmental sustainability.